2020
DOI: 10.3390/ani10112143
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing and Antimicrobial Susceptibility Profile of Staphylococcus aureus Isolates Recovered from Bovine Mastitis and Nasal Samples

Abstract: In the present study, we aimed to determine the antimicrobial resistance and molecular typing of Staphylococcus aureus recovered from transient and persistent intramammary infections and nares/muzzles in dairy cows. We investigated the antimicrobial resistance of 189 S. aureus strains using a broad antimicrobial susceptibility profile. Furthermore, 107 S. aureus isolates were strain-typed using staphylococcal protein-A (spa) typing. A large proportion of strains exhibited multidrug resistance to antimicrobials… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…The produced synthetic genes were cloned into the pUC57 vector and then sub-cloned into the pET28a expression vector [ 16 ]. Recombinant plasmids were used to transform the expression strain E. coli BL21-Star™(DE3) as previously described [ 17 ] with modifications. Briefly, transformed E. coli BL21-Star™(DE3) were selected on kanamycin plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The produced synthetic genes were cloned into the pUC57 vector and then sub-cloned into the pET28a expression vector [ 16 ]. Recombinant plasmids were used to transform the expression strain E. coli BL21-Star™(DE3) as previously described [ 17 ] with modifications. Briefly, transformed E. coli BL21-Star™(DE3) were selected on kanamycin plates.…”
Section: Methodsmentioning
confidence: 99%
“…An udder adapted S. aureus isolate originated from a case of chronic subclinical IMI was used [ 17 ]. Staphylococcus aureus (spa typing t605) inoculum was prepared as previously described [ 20 ] with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve Staphylococcus aureus isolates originating from aseptically collected milk samples (n = 6) and noses (n = 6) obtained from 2 Brazilian dairy herds (Souza et al, 2016a;Cunha et al, 2020;Santos et al, 2020) were available. These isolates were previously identified phenotypically by biochemical tests (Souza et al, 2016a), confirmed by MALDI-TOF MS and molecular identification targeting a portion of the conserved S. aureus thermonuclease gene (Santos et al, 2020).…”
Section: Staphylococcal Isolatesmentioning
confidence: 99%
“…Twelve Staphylococcus aureus isolates originating from aseptically collected milk samples (n = 6) and noses (n = 6) obtained from 2 Brazilian dairy herds (Souza et al, 2016a;Cunha et al, 2020;Santos et al, 2020) were available. These isolates were previously identified phenotypically by biochemical tests (Souza et al, 2016a), confirmed by MALDI-TOF MS and molecular identification targeting a portion of the conserved S. aureus thermonuclease gene (Santos et al, 2020). Additionally, a collection of 38 different NAS isolates obtained from 13 Flemish dairy herds during previous studies (Piessens et al, 2011;Supré et al, 2011;De Visscher et al, 2016) was available as well: 5 S. chromogenes isolates originating from teat apices (TA; De , 10 S. chromogenes isolates originating from aseptically collected milk samples (Supré et al, 2011), 5 Staphylococcus haemolyticus isolates originating from TA (De Visscher et al, 2016), 5 S. haemolyticus isolates from aseptically collected milk samples (Supré et al, 2011), 5 S. fleurettii isolates originating from aseptically collected milk samples (Supré et al, 2011), and 8 S. fleurettii isolates originating from cows' environment (Piessens et al, 2011).…”
Section: Staphylococcal Isolatesmentioning
confidence: 99%
“…One of the most common bovine mastitis pathogens is Staphylococcus aureus, which is a notable issue for dairy farming due to its pathogenicity, contagiousness, the likelihood of persistence in the form of intramammary infections, and poor cure rates associated with current antimicrobial therapies; this pathogen has unquestionable importance in veterinary and human medicine [1][2][3]. This bacterium is also known to be part of the skin microbiota [4,5].…”
Section: Introductionmentioning
confidence: 99%